Internet Autonomous Systems (ASes) Level Topology Modeling (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to develop a prediction model for Autonomous systems (ASes) internet growth.The Border Gateway Protocol (BGP) is taken as primary data source. BGP raw data (RIBS) collected from Universityof Oregon Route Views Project Archive. Data from 2001 to 2009 are used in this study. Statistical methods areapplied to analyse the collected data. A model is developed based on the outcome of the data analysis. It is found thatthe internet growth follows Logistic Regression Model with a rate of growth equal 0.014. The link growth is alsoinvestigated and found to have followed an exponential pattern with a rate of growth equal 0.017.